Tropienie tożsamości - inspiracje językoznawcze = Tracing Identity: Linguistic Inspirations - Steciąg, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Studies on Identity are contemporary very large and cover wide range of scientific disciplines, i.e. linguistics. The problem of manifestation of identity in language is especially interesting for the linguists.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie